Assessment of environmental risks to the Voronezh Oblast public health resulted from contamination of drinking water sources - Anatasia S. Boeva; Tatiana I. Prozhorina; Anna G. Baskakova (Водное хозяйство России: проблемы, технологии, управление)
The relevance of research is particularly high for the Central Black Earth Region due to the high population density and the presence of numerous dispersed sources of environmental risk with a chemical type of impact on natural waters. People are forced to use water that does not meet health standards for drinking purposes, which poses a serious threat to their health. The article presents the results of calculating the non-carcinogenic risk from exposure of the body to priority chemicals (iron, manganese, nitrates) contained in the drinking water supply sources of the region, based on average annual concentrations at 174 monitoring points of control (m.t.c.) of the distribution network in settlements Voronezh Oblast.